Consumption-based forecasting and planning : predicting changing demand patterns in the new digital economy - Chase, Charles (Wiley and SAS business series., 2021)
"Helps companies understand the short-term changes in consumer demand patterns as a result of the digital economy, and COVID-19. Also, what is driving those changing consumer demand patterns (price, sales promotions, in-store merchandizing, epidemiological, economic and other related factors like unplanned events related to the pandemic crisis). Provides real case examples using real data, and how to apply advanced analytics and machine learning to solve current business problems. Provides a framework for changing the way demand forecasting and planning are done, as well as the change management requirements for sustainability"--